Historical Analysis of Bibliometric Trends in the Journal of Pediatric Orthopaedics With a Particular Focus on Sex. Issue 3 (March 2018) - Fischer, James P.; Wininger, Austin E.; Scofield, David C.; Tucker, Aamir; Kacena-Merrell, Ethan J.; Whipple, Elizabeth C.; Kacena, Melissa A.; Loder, Randall T.
Abstract : Background: Orthopaedics is the clinical discipline with the lowest percentage of female residents and faculty. Pediatric orthopaedics has a higher percentage of women than other orthopaedic subspecialties. It was the purpose of this study to examine bibliometric trends in the Journal of Pediatric Orthopaedics (JPO) with a specific focus on sex. Methods: A bibliometeric analysis for the years 2015, 2005, 1995, 1985, 1981 was performed. The names of first and corresponding authors; corresponding author position; country of origin; number of institutions, countries, authors, printed pages, and references was tabulated. Author sex was identified for the first and corresponding authors using the "Baby Name Guesser" (www.gpeters.com/names/baby-names.php ). A P <0.05 was considered significant. Results: There were 746 publications; 68.7% were from North America. The average number of authors, corresponding author position, collaborating institutions, countries, and number of references increased, whereas the number of printed pages decreased. Asia had the greatest number of authors (4.4), with Australia/New Zealand the fewest (3.4). Sex was determined for 98.3% of the first authors and 98.5% of the corresponding authors. There was a significant increase in the number of female first authors over time (5.9% to 25.6%, P <10 −6 ), especially in Europe and North America. There were significant increase in the number of female corresponding authors over time (5.8% to 17.6%, P =0.000009). There was a significant trend to have a greater percentage of both female first and corresponding authors over time ( P =0.0005) with a reverse trend for both male first and corresponding authors ( P <10 −6 ). Conclusions: In this study, we noted that the number of female first and corresponding authors in Journal of Pediatric Orthopaedics has been steadily increasing. This should result in more female pediatric orthopaedic surgeons in academic faculty positions. Abstract : Supplemental Digital Content is available in the text.